Nickel Slag/Laterite Soil and Nickel Slag/Iron Sand Nanocomposites: Structural, Optical, and Electromagnetic Absorption Properties - Heryanto, Heryanto; Siswanto, Siswanto; Rahmat, Roni; Sulieman, Abdelmoneim; Bradley, D.A. *; Tahir, Dahlang (American Chemical Society, 2023)
Efforts to produce microwave absorber materials that are inexpensive and environmentally friendly have become a means of greening the environment. The breakthrough can be focused on industrial waste and natural materials for functional purposes and how to enhance their performance. We successfully synthesized nickel slag/laterite soil (NS/LS) and nickel slag/iron sand (NS/IS) nanocomposites using a simple mechanical alloying technique, and the electromagnetic (EM) wave absorption capacities of the nanocomposites were measured using a vector network analyzer. The structural properties of the nanocomposites were analyzed by X-ray diffraction spectroscopy, where the results of the analysis showed that NS/IS has the largest crystallite size (15.69 nm) and the highest EM wave absorption performance. The optical properties of the nanocomposites were determined from their Fourier transform infrared spectra using the Kramers–Kronig relation. As determined through a quantitative analysis of the optical properties, the distance between the longitudinal and transversal optical phonon wavenumber positions (Δ(LO – TO) = 65 cm–1) is inversely proportional to the reflection loss. The surface morphologies of the nanocomposites were analyzed by scanning electron microscopy, and the particle diameters were observed by binary image and Gaussian distribution analyses. The nanocomposite surface exhibits a graded-like morphology, which indicates multiple reflections of the EM radiation, consequently reducing the EM interference. The best nanocomposite for an attenuated EM wave achieved a reflection loss of −39.14 dB at 5–8 GHz. A low penetration depth has implications for the electrical charge tuning of the storage and composite magnets. Finally, the EM absorption properties of NS/IS and NS/LS indicate a 2-mm-thick environmentally friendly nanocomposite for EM absorption.